RELN and VLDLR mutations underlie two distinguishable clinico‐radiological phenotypes. Issue 6 (29th April 2016) - Valence, S.; Garel, C.; Barth, M.; Toutain, A.; Paris, C.; Amsallem, D.; Barthez, M.‐A.; Mayer, M.; Rodriguez, D.; Burglen, L.
Abstract : Abstract : Pontocerebellar hypoplasias (PCH) are characterized by lack of development and/or early neurodegeneration of cerebellum and brainstem. We report five patients referred for PCH, showing atypical clinical and magnetic resonance imaging (MRI) features suggestive of defects in the Reelin pathway. We screened for mutations in RELN or VLDLR and compared the phenotype of these patients with that of previously reported patients. All patients had profound cerebellar hypoplasia on MRI with peculiar cerebellar morphology, associated with flattened pons and neocortical abnormalities. Patient 1 had profound motor and intellectual disability with moderate lissencephaly suggestive of RELN mutations and was shown to harbor a splicing homozygous RELN mutation. The four other patients had a milder phenotype consistent with CARMQ1 (cerebellar ataxia and mental retardation with or without quadrupedal locomotion). These patients showed mild simplification or thickening of cortical gyration and had VLDLR mutations. Reelin signaling regulates neuronal migration in the developing mammalian brain. VLDLR is a key component of the Reelin pathway. Our patients had a very small and dysplatic cerebellar vermis that should suggest the involvement of these genes. Moreover, differences in clinical severity, involvement of the cerebellar hemispheres, together with the severity of the neocortical defect, enables RELN ‐mutated patients to be distinguished from VLDLR ‐mutated patients.